"I will not hate myself because you cannot accept me": Problematizing empowerment and gender-diverse selfies. (3rd April 2017) - Vivienne, Son
ABSTRACT: While selfies of beautiful cisgender women are declaimed by mainstream media as narcissistic and facile, some body-positive feminists and queer theorists argue that selfies can be empowering. They claim self-representation by traditionally stigmatized people can challenge normative presentations of beauty and gender. This article problematizes "empowerment" as a definitive and/or productive frame and argues instead for observation and analysis of "privilege" in situated practice. In this article I combine analysis of a collection of online cultural artifacts (including nonbinary selfies on Tumblr) and interviews with a small group of trans* social media storytellers to explore theoretical tensions between gender fluidity and identity fragmentation across multiple social media sites and practices. Gender-diverse digital self-representation encompasses both "consistent" androgyny, nonbinary, agender, and so on, and "emergent" presentations-in-flux. I assert that the ongoing iteration of self across social media—implied by self (re)presentation—can have simultaneous and contradictory political significance. I conclude that networked interpersonal complications frame understandings of empowerment, as perhaps they always have done.